Pengaruh Profesionalisme dan Independensi Auditor Internal Terhadap Penerapan Good Government Governance - Ketut Tanti Kustina; Agung Gede Wikantara; I Gusti Ayu Diah Utari; Desak Made Sukarnasih (Universitas Warmadewa, 2022)
The purpose of this study was to determine the effect of professionalism and independence of internal auditors on the implementation of good government governance (GGG) in the Regional Government of Bali Province. The population of this study was 57 auditor samples used were 45. The source of the data used is primary data with the sampling method is saturated sampling method. Data collection techniques using a questionnaire (questionnaire) distributed at the Inspectorate of the Province of Bali. The analysis in this study conducted a descriptive analysis. Descriptive analysis looks at respondent characteristic data and descriptive data. In the test instrument all indicators are declared valid and reliable, then proceed with the classic assumption test the entire data meets the qualifications required in the hypothesis test. The coefficient of determination of the model is 46.8% which can be explained in the model and 53.2% is explained outside the model, then a partial test of 0.043 professionalism and 0.005 independence has a significant positive effect on good government governance.